IoT security paradigms and applications : research and practices - Sharma, Sudhir Kumar; Bhushan, Bharat (Software specialist); Debnath, N. C. (Narayan C.) (Boca Raton : CRC Press, 2021)
"Integration of IoT (Internet of Things) with Big data and cloud computing has brought forward numerous advantages and challenges such as data analytics, integration and storage. Present book highlights these challenges and provide an integrating framework for these technologies illustrating role of blockchain in all the possible facets of IoT security. Further, it investigates the security and privacy issues associated with various IoT systems along with exploring various machine learning based IoT security solutions. It brings together state-of-the-art innovations, research activities (both in academia and industry), and the corresponding standardization impacts of 5G as well"--
OCLC-licensed vendor bibliographic record.
Keywords: Internet of things; COMPUTERS / Networking / General; COMPUTERS / Security / General; COMPUTERS / Computer Engineering